Tom Jaine, translator, The French Country Housewife: The First Volume of Maison rustique des dames (1859) by Cora Millet-Robinet - Dalby, Andrew (Petits Propos Culinaires, 2021)
Tom Jaine, translator, The French Country Housewife: The First Volume of Maison rustique des dames (1859) by Cora Millet-Robinet: Prospect Books, 2017: 711 pp., hardback, £35.00.